Haplotype structure of CYP2B6 and association with plasma efavirenz concentrations in a Chilean HIV cohort - Carr, Daniel F. (Oxford University Press, 2010)
OBJECTIVES: Efavirenz is extensively metabolized by CYP2B6, and associations between CYP2B6 polymorphisms and plasma efavirenz exposure have been reported. The objective of this study was to investigate CYP2B6 haplotype structure and functional consequences in a Latin American population. PATIENTS AND METHODS: Two hundred and nineteen patients were recruited at Fundación Arriarán, Chile, between September and December 2008. Plasma efavirenz concentrations were determined using liquid chromatography with mass spectrometry. Genotyping for 30 single nucleotide polymorphisms (SNPs) with a minor allele frequency of >0.05 in the HapMap CEU population at intervals of ∼1 kb across the CYP2B6 locus was conducted using Sequenom iPLEX MALDI-TOF. RESULTS: Thirteen SNPs passed quality control and, of these, statistically significant associations (P < 0.001) with plasma efavirenz concentrations were observed for 11. Pairwise tagging SNP analysis (R(2) > 0.8) identified 3 SNPs (rs10403955, rs2279345 and rs8192719) representative of the 11 associated SNPs. A composite genetic model of these three alleles was constructed, and an association between carriers of four to six of these alleles and the risk of efavirenz plasma concentrations >4 µg/mL was identified with an odds ratio of 48.1 (95% confidence interval: 13.5–207.7). This represents a positive predictive value of 80.9% and a negative predictive value of 91.8%, with sensitivity of 57.9% and specificity of 97.2%. CONCLUSIONS: A composite genetic model of CYP2B6 SNPs in a Chilean HIV-positive cohort may have value in predicting concentrations of efavirenz associated with a higher likelihood of CNS toxicity. Further investigation of the functional basis of these associations is now required.